(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Haemorrhoids are defined as the dilated veins within anal canal in the sub epithelial region formed by radicles of superior, middle and inferior rectal veins. Based on the degree of prolapse, they are classified into 1st, 2nd, 3rd, and 4th degree haemorrhoids. According to Ayurvedic classics, it can be correlated with Arshas; the muscular sprouts torture the person in the same way that enemies do. Acharya Susruta mentioned four therapeutic measures such as Bheṣhaja, Kṣhara, Agni and Sastra karma in the management of Arshas. Ligation and excision, Laser therapy, Sub mucosal haemorrhoidectomy are the commonly done procedure in the management of third-degree haemorrhoids. But these are often associated with post operative complications like Pain, Secondary haemorrhage, Urinary retention, Bowel incontinence and Recurrence. Kshara Karma is a proven para-surgical procedure for the management of Arshas. It is minimally invasive, cost effective, requires less hospital stay and having less complications. In the present study, Apamarga Pratisaraniya Teekshna Kshara was applied in a third-degree internal haemorrhoids. The assessment was done as per the subjective and objective criteria and anal speculum examinations, daily up to one week and follow up done on 15th and 30th days. It was found that Apamarga Pratisaraniya Teekshna Kshara is effective in the management of third-degree internal haemorrhoids. Symptoms like bleeding per rectum, prolapse of the mass, and pain got significantly reduced on 30th day. From this study, it can be concluded that, Apamarga Pratisaraniya Kshara Karma is an effective treatment in the management of third-degree internal haemorrhoid.